Rancangan Aplikasi Pembelajaran Angklung Untuk SLB Bagian B Tuna Rungu Berbasis Android - Diana Effendi; Bella Hardiyana (Universitas Islam Sumatera Utara, 2019)
The introduction of angklung music especially for deaf students is done by replacing numeric notes with various hand movements by the teacher. It takes two teachers to produce harmonious music with one teacher focusing on melody and the other teacher focusing on chords. However, hand movements are still limited to ordinary notes. The teacher's hand movements do not yet include the crescendo and decrescence notes. In addition, if one of the teachers is unable to attend, it cannot produce a harmonious music. To overcome this, multimedia-based angklung learning aids and android-based applications are made, where multimedia allows an angklung game to be carried out without the help of a trainer. In addition, created a partitur reading with the android application to enhance the students' ability to practice outside hours. But in these discussions only discuss the design of the android based angklung application used Unified Modeling Language (UML) diagram.. This research was funded by Direktorat Riset dan Pengabdian Kepada Masyarakat, Direktorat Jenderal Penguatan Riset dan Pengembangan , Kementrian Pendidikan dan Kebudayaan No : 108/SP2H/PPM/DPRM/2019, 08 March 2019